KEPATUHAN PELAPORAN SPT TAHUNAN WAJIB PAJAK ORANG PRIBADI DAN FAKTOR-FAKTOR YANG MEMPENGARUHINYA - Intan Erlita Sari; Pariandari -; Moh. Abdurrosyid (Fakultas Ekonomi dan Bisnis Universitas Islam As-Syafi'iyah, 2023)
This study aims to examine the effect of the implementation of e-filing and tax sanctions on taxpayer compliance with annual tax returns. The independent variable in this study is the application of e-filing and tax sanctions, while the dependent variable is taxpayer compliance. The population of this study includes individual taxpayers who are registered at KPP Pratama Pondok Gede. Samples were taken using purposive sampling method with certain criteria, during the study period there were 113 samples. The results show that the implementation of e-filing has a significant positive effect on taxpayer compliance and tax sanctions have a significant positive effect on taxpayer compliance.